SILOS. Źródło wiedzy o przeszłości dla przyszłości - Szefliński, Piotr; Krzepkowski, Sebastian (My University, 2006)
The experience gained during operation of the Horizon Integrated Library System within the Academic Library Network of Łódź shows that the standard statistics offered by the system do not fully satisfy the expectations of the librarians. The available data are aggregated in some way and even though they are collected every day, they do not provide answer for each question. For this reason, in the Institute of the Academic Library Network SILOS system came into existence, which meets the demand of the librarians for statistical data today and tomorrow. This is the data warehouse, which daily archives the current status of the system and borrowings in the form allowing for further analysis. It provides the librarians with the possibility of asking statistical questions without any limitations as for the time and thematic field, as well as the questions they will be aware of in next years. SILOS provides the data that can be used for evaluation of the changes in regard to the operation of the library system within a period of time, and in this way it may be useful in forecasting the future preferences of the readers, including substantial and organisational ones.

Doświadczenia zdobyte przy eksploatacji systemu bibliotecznego Horizon w Łódzkiej Akademickiej Sieci Bibliotecznej wskazują, że standardowe statystyki oferowane przez system nie w pełni zaspokajają potrzeby bibliotekarzy. Dostępne dane są w pewien sposób zagregowane i nawet ich codzienne gromadzenie nie zapewnia uzyskania odpowiedzi na każde pytanie. Dlatego w Zakładzie Akademickiej Sieci Bibliotecznej powstał system SILOS, który wychodzi naprzeciw zapotrzebowaniu bibliotek na dane statystyczne dziś i jutro. Jest to hurtownia danych, która codziennie archiwizuje stan systemu i wypożyczeń w formie umożliwiającej ich dalszą analizę. Zapewnia bibliotekarzom teraz i w przyszłości możliwość stawiania pytań statystycznych bez ograniczeń, w dowolnych przekrojach czasowych i tematycznych; również pytań, co do których dopiero w następnych latach będą wiedzieli, że powinni je postawić. SILOS dostarcza dane, które mogą służyć do oceny przemian, jakie zachodzą w wykorzystaniu systemu bibliotecznego na przestrzeni czasu, a tym samym może pomóc prognozować przyszłe preferencje czytelników zarówno merytoryczne jak i organizacyjne.
SILOS – the source of knowledge about the past for the future purposes